Genetic analysis of metabolic traits in an intercross between 8-week body-weight selected chicken lines - Ek, Weronica (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2007)
Metabolic traits are of paramount importance in agricultural production, as this group includes most traits of economic interest in livestock improvement. Examples include growth rate, feed efficiency and fat deposition. An improved understanding of the genetic basis of these traits can both improve our understanding of the genes that have been under selection and identify genes and pathways to be included in future breeding programs.